MODEL PELATIHAN SISWA PUTUS SEKOLAH STUDI KASUS PADA BALAI LATIHAN KERJA PROPINSI BENGKULU - Syaiful Anwar AB (Unib Press Universitas Bengkulu, 2017)
The purpose of this research is to test the influence of the quality of service to the satisfaction of the training participants at Balai Latikan Kerja (BLK) in Bengkulu Province. The method used in this research is survey with interview approach to get observation data directly. The results of this study indicate that the role of instructors (HR) and methods greatly affect the success of trainees in the future. The positive impact of good service will increase customer satisfaction and loyalty as well as the desire to re-buy, which will increase the income received from the products sold. In order to compete, survive, and grow, the organization is required to be able to meet the needs and desires of customers by providing the best service and quality. Based on the strengths, weaknesses, opportunities and threats that may occur, then the biggest weakness is the quality of instructors and learning space into the greatest weakness.Keywords: service quality, satisfaction , SWOT analysis.